Efektivitas Pelaksanaan Tsunami Safe Zone Terhadap Masyarakat KotaPadang - Andina Zaler; Nora Eka Putri (Jurnal Teori dan Riset Administrasi Publik, 2022)
An earthquake with the potential for a tsunami is a disaster that needs to be anticipated, especially the city of Padang, which is an earthquake-prone area with the potential for a tsunami. Considering the potential for this very dangerous disaster, of course it is necessary to make efforts to reduce disaster risk in order to prevent or at least anticipate the number of victims, both property and human life. Efforts to reduce disaster risk for the safety of human life, when an earthquake with a potential tsunami occurs, tsunami evacuation instructions have been installed by the Padang City Regional Disaster Management Agency, one of which is by making a blue line (Tsunami Safe Zone). The blue line (Tsunami Safe Zone) is an estimate of the area classified as safe from a potential tsunami. This blue line will later indicate that if residents have crossed the line, they will be in a tsunami-safe area. Keywords: effectiviness, tsunami, safe zone